2016
DOI: 10.1016/j.pmedr.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum lipid management between elderly and non-elderly patients with and without coronary heart disease (CHD)

Abstract: Serum lipid management in patients aged ≥ 75 has not been precisely explored. We, therefore, compared the serum lipid management between the two age groups with and without coronary heart disease (CHD).We, therefore, retrospectively reviewed medical charts of patients who were hospitalized in the departments of internal medicine during a period of 14 months. Serum lipid goal attainment was explored by applying the lipid goals for patients aged < 75 to those aged ≥ 75.In 1988 enrolled patients, 717 subjects (36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Clinically, it is divided into stable CHD and acute coronary syndrome. Although epidemiological studies have shown that classical risk factors such as high blood lipids [ 13 15 ], high blood pressure [ 16 , 17 ], smoking [ 18 23 ], obesity [ 24 29 ], and diabetes [ 30 33 ] lead to CHD, its etiology is not fully understood. In recent years, these traditional risk factors have been effectively reduced, but the incidence of AS is still high [ 33 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, it is divided into stable CHD and acute coronary syndrome. Although epidemiological studies have shown that classical risk factors such as high blood lipids [ 13 15 ], high blood pressure [ 16 , 17 ], smoking [ 18 23 ], obesity [ 24 29 ], and diabetes [ 30 33 ] lead to CHD, its etiology is not fully understood. In recent years, these traditional risk factors have been effectively reduced, but the incidence of AS is still high [ 33 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reduction in serum cholesterol levels have been shown to be effective to prevent ASCVD 1,2) ; however, serum LDL-C goal attainment was not necessarily desirable. 3,4) Serum LDL-C levels are mostly regulated by endocytosis of LDL via hepatic LDL receptors (LDLR). 5,6) Cell-surface expression of LDLR depends upon transcriptional activation by sterol responsible element binding protein 2 (SREBP2), as well as post-translational regulation (protein degradation) by pro-protein convertase subtilisinkexin type 9 (PCSK9) and inducible degrader of LDL receptor (IDOL), an E3-ubiquitin ligase, which are activated by SREBP2 and liver X receptor (LXR), respectively.…”
Section: Introductionmentioning
confidence: 99%